Zur Kenntnis der Gattung Exochomoscirtes Pic, 1916 (Coleoptera, Scirtidae) (153. Beitrag zur Kenntnis der Scirtidae). - Klausnitzer, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 2010)
The genus Exochomoscirtes Pic, 1916 is characterized, and three new species are described: E. heinrichdathei n. sp. (Laos), E. holgerdathei n. sp. (north-east India) and E. sondaicus n. sp. (Java). The number of known Exochomoscirtes is thereby increased to 38. Nomenclatural Acts heinrichdathei Klausnitzer, 2010 (Exochomoscirtes), spec. nov. holgerdathei Klausnitzer, 2010 (Exochomoscirtes), spec. nov. sondaicus Klausnitzer, 2010 (Exochomoscirtes), spec. nov.